Characterization and photocatalytic behavior of 2, 9-di(aryl)-1, 10-phenanthroline copper(i) complexes. Issue 20 (2nd May 2017) - Cetin, M. Mustafa; Hodson, Roman T.; Hart, C. Robin; Cordes, David B.; Findlater, Michael; Casadonte Jr., Dominick J.; Cozzolino, Anthony F.; Mayer, Michael F.
Abstract : The synthesis, photophysical properties, and theoretical calculations of 2, 9-di(aryl)-1, 10-phenanthroline copper(i ) complexes are described along with application to a photocatalytic ATRA reaction. Abstract : The synthesis, characterization, photophysical properties, theoretical calculations, and catalytic applications of 2, 9-di(aryl)-1, 10-phenanthroline copper(i ) complexes are described. Specifically, this study made use of di(aryl)-1, 10-phenanthroline ligands including 2, 9-di(4-methoxyphenyl)-1, 10-phenanthroline (1 ), 2, 9-di(4-hydroxyphenyl)-1, 10-phenanthroline (2 ), 2, 9-di(4-methoxy-3-methylphenyl)-1, 10-phenanthroline (3 ), and 2, 9-di(4-hydroxy-3-methylphenyl)-1, 10-phenanthroline (4 ). The 2 : 1 ligand-to-metal complexes, as PF6 − salts, i.e., ([Cu·(1 )2 ]PF6, [Cu·(2 )2 ]PF6, [Cu·(3 )2 ]PF6, and [Cu·(4 )2 ]PF6 ) have been isolated and characterized. The structures of ligands1 and2 and complexes [Cu·(1 )2 ]PF6 and [Cu·(3 )2 ]PF6 have been determined by single-crystal X-ray analysis. The photoredox catalytic activity of these copper(i ) complexes was investigated in an atom-transfer radical-addition (ATRA) reaction and the results showed fairly efficient activity, with a strong wavelength dependence. In order to better understand the observed catalytic activity, photophysical emission and absorption studies, and DFT calculations were also performed. It was determined that when the excitation wavelength was appropriate for exciting into the LUMO+1 or LUMO+2, catalysis would occur. On the contrary, excitations into the LUMO resulted in no observable catalysis. In light of these results, a mechanism for the ATRA photoredox catalytic cycle has been proposed.